Interactions between trace metals (Cu, Hg, Ni, Pb) and 2,3,7,8-tetrachlorodibenzo-p-dioxin in the antarctic fish Trematomus bernacchii: Oxidative effects on biotransformation pathway - Benedetti, Maura; Fattorini, Daniele; Martuccio, Giacomo; Nigro, Marco; Regoli, Francesco (Environmental Toxicology and Chemistry, 2009)
Abstract Biological effects of chemical mixtures are an emerging issue when using biomarkers in field conditions, because synergistic or inhibitory interactions, cascade, and indirect mechanisms can both enhance or suppress responses to specific classes of pollutants. The Antarctic rock cod (Trematomus bernacchii) was exposed to various trace metals (Cu, Hg, Ni, and Pb) and to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), dosed alone or in combination, to generate hypotheses regarding the mechanisms of action at the cellular level. Concentrations of metals significantly increased in liver of T. bernacchii without significant differences between organisms exposed only to the elements or cotreated with TCDD. The marked induction of cytochrome P450 (CYP) by TCDD was greatly suppressed by cotreatment with Cu at both catalytic and protein expression levels, whereas no significant effects were caused by coexposures with Hg, Ni, and Pb. The oxidative status was measured by integrating individual antioxidants with the total oxyradical scavenging capacity toward peroxyl radicals (ROO·) and hydroxyl radicals (·OH). Synergistic oxidative effects appeared in fish coexposed to Cu and TCDD, suggesting that biotransformation efficiency is down-regulated by higher levels of hydrogen peroxide, hydroxyl radicals, and/or mechanisms limiting availability of heme groups. Major oxidative perturbations also were observed in organisms coexposed to TCDD and Hg; in these organisms, however, the marked increase of glutathione content could explain the absence of oxidative inhibition of the CYP system. More limited oxidative effects were caused by Ni and Pb, and the contemporary absence of inhibitory effects on CYP would further confirm the importance of pro-oxidant mechanisms in modulating the biotransformation pathway. The overall results indicate that a wide battery of biomarkers is necessary to assess the impact of chemical mixtures in field conditions.